Case Report: Refractory Listeria innocua Meningoencephalitis in a Three-Year-Old Boy - Liao, Yi; Liu, Lingling; Zhou, Hua; Fang, Feng; Liu, Xinglou (Frontiers in Pediatrics, 2022)
Listeria innocua is widely distributed in the environment and food, which is considered as a non-pathogenic bacterium for both human and animals. To our knowledge, only a few cases of Listeria innocua infection in humans and ruminants have been reported. Moreover, there has been no report on human Listeria innocua meningoencephalitis. Here, we report a case of severe refractory meningoencephalitis in a three-year-old boy after infection with Listeria innocua. The child’s first symptoms were runny nose, high fever, and rashes, which quickly progressed to unconsciousness and convulsions. The initial analysis of cerebral spinal fluid revealed remarkably elevated protein level and increased white blood cells count. And the blood culture of the patient in the early stage was positive for Listeria innocua. In addition, his brain imaging tests were observed dynamically, and the result showed a speedy progression from multiple intracranial abnormal signals to hydrocephalus and interstitial cerebral edema. After receiving antibiotics and symptomatic treatment for nearly three months, the patient's condition improved markedly. However, he still had residual complications such as hydrocephalus. Although Listeria innocua is considered harmless, it can still cause disease in humans, even severe meningoencephalitis, with rapid progression and poor prognosis. Early discovery, diagnosis and treatment are necessary to elevate the survival rate and life quality of those patients. Antibiotics should be used with sufficient duration and dosage. Cephalosporins are not suitable for the treatment of Listeria innocua meningoencephalitis and penicillin antibiotics are preferred for children. The presentation of this case will help to expand our knowledge of Listeria infections and provide a potential candidate for pathogens causing severe childhood central nervous system infection.